Peran Kecerdasan Buatan dalam Efisiensi Desain Bangunan - Palakka; Muh. Risqy Mutawakkil; Muhammad Arbaim Asridal; Muhammad Taufiq Urinta; Muhammad Fildam Anugrah (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This research discusses the role of artificial intelligence (AI) in increasing the efficiency of architectural design. The use of AI in architecture has had a positive impact in terms of optimizing the creative process, fast data analysis and improving the overall quality of the design. This study analyzes various AI methods used in architectural design, as well as their results and impact on speed and accuracy in producing efficient designs. In conclusion, AI has great potential to change the paradigm in industrial architecture and bring significant efficiencies